2017
DOI: 10.3389/fcimb.2017.00177
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Mycoplasma bovis Strains Reveals That Decreased Virulence with Increasing Passages Might Correlate with Potential Virulence-Related Factors

Abstract: Mycoplasma bovis is an important cause of bovine respiratory disease worldwide. To understand its virulence mechanisms, we sequenced three attenuated M. bovis strains, P115, P150, and P180, which were passaged in vitro 115, 150, and 180 times, respectively, and exhibited progressively decreasing virulence. Comparative genomics was performed among the wild-type M. bovis HB0801 (P1) strain and the P115, P150, and P180 strains, and one 14.2-kb deleted region covering 14 genes was detected in the passaged strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 48 publications
2
31
0
1
Order By: Relevance
“…Completely assembled genome sequences have been determined for twelve M. bovis isolates (including four derived from highly passaged isolates from strain HB0801 [Rasheed et al., ]), with draft genomes available for 20 additional strains (NCBI database on 24 January 2018). To date, detailed comparative genomic analyses have only been reported on the first three complete M. bovis genomes to be sequenced (Li et al., ; Qi et al., ; Wise et al., ) and for the high‐passage derivatives of HB0801 (Rasheed et al., ). Although the overall genomic framework and gene synteny are largely conserved, these are punctuated by incursions of integrative conjugative elements (ICE), variable copy numbers and integration sites of insertion sequences (IS) and a large chromosomal inversion in the PG45 type strain (generated by recombination between two IS units).…”
Section: The Causative Organismmentioning
confidence: 99%
See 2 more Smart Citations
“…Completely assembled genome sequences have been determined for twelve M. bovis isolates (including four derived from highly passaged isolates from strain HB0801 [Rasheed et al., ]), with draft genomes available for 20 additional strains (NCBI database on 24 January 2018). To date, detailed comparative genomic analyses have only been reported on the first three complete M. bovis genomes to be sequenced (Li et al., ; Qi et al., ; Wise et al., ) and for the high‐passage derivatives of HB0801 (Rasheed et al., ). Although the overall genomic framework and gene synteny are largely conserved, these are punctuated by incursions of integrative conjugative elements (ICE), variable copy numbers and integration sites of insertion sequences (IS) and a large chromosomal inversion in the PG45 type strain (generated by recombination between two IS units).…”
Section: The Causative Organismmentioning
confidence: 99%
“…To date, only one study has been reported in which it was possible to correlate specific genes with pathogenicity. By comparing 115‐, 150‐ and 180‐passage isolates (with decreasing pathogenicity) to the parental HB0801 isolate, ten metabolism‐related genes together with one variable surface protein‐encoding gene were identified as germane to the observed attenuation (Rasheed et al., ). However, no gene has been unambiguously demonstrated to influence the virulence profile of any M. bovis isolate in vivo .…”
Section: The Causative Organismmentioning
confidence: 99%
See 1 more Smart Citation
“…The M. bovis strains were cultured in PPLO broth BD DifcoTM, US California [4,20]. M. bovis genomic DNA was extracted using a bacterial DNA extraction kit (Tiangen, Beijing, China) [21].…”
Section: Cultivation and Identi Cation Of M Bovismentioning
confidence: 99%
“…Comprehensive investigation of pathogenesis of M. bovis was sought and began in 2008 in China with the identification and isolation of M. bovis strain HB0801 from calf lung lesions in the Hubei province (Lei et al, 2008). Consequently, complete genome sequencing of the HB0801 strain and its comparison with the genomes of other strains and Mycoplasmas species laid down a foundation for the clarification of pathogenesis of M. bovis (Qi et al, 2012;Rasheed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%